English secondary textbook, values transmission and the Islamic identity : a case study of the International Islamic School Malaysia (Secondary), Gombak - Nor Hayati binti Husin (Kulliyyah of Education, International Islamic University Malaysia, 2017)
The worldwide spread of the English language has become an inevitable result of today's globalized world. The globalization of the English language has penetrated many non-native countries. Consequently, the global status of English and the necessity to learn it has resulted in mass production of English language textbooks with the dominant ownership by the Western regions. This has given the English language textbooks a pivotal role in conveying the English language skills. However, language and culture are inseparable complements, and both are the conduit through which values are disseminated. Therefore, the contents of English language textbooks communicate the values embedded in the culture presented therein. This study aims to explore the values transmitted in selected English language textbooks used at the International Islamic School Malaysia Secondary (IISMS) and its effect on students' perception of the Islamic identity. A textual analysis of the Cambridge Checkpoint English textbooks for Grades 7, 8, and 9 was conducted to identify the values present therein. This case study explored the perceptions of students and English teachers about the values transmitted in the English language textbooks, and how they preserve the Islamic identity while adopting the International curriculum of Cambridge. The findings of the textbook analysis indicate that the context of the English taught is not only for the language skills but also to transmit certain values; some of which are suitable for Muslims but most contradict the Islamic teachings. The values conveyed were done implicitly and explicitly in a systematic way by presenting a range of text-types, factual articles, pictures, and symbols in the textbooks. The findings were strengthened by interviewing students and teachers as well as observing them during English lessons about this issue. The results show that the teachers and students have only partial understanding and awareness of the values transmitted in the English language textbooks. The lack of awareness among the students was related to the low awareness held by teachers about the function of the English language textbooks as a means of disseminating both formal and informal knowledge to students as well as a powerful academic source in propagating the culture and values mainly from the Western perspectives. This led to the creation of a state of alienation and confusion within the students while dealing with those values especially the ones which contradict with the Islamic teachings.